TRANSFORMING VOCATIONAL EDUCATION THROUGH ARTIFICIAL INTELLIGENCE: COMPETENCY DEVELOPMENT FOR THE DIGITAL ECONOMY - Jalilova Muxtasar Karimjonovna; Rahmatullayeva Umida Mahamadjon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract Artificial Intelligence (AI) technologies are rapidly transforming vocational education systems worldwide by enabling the development of competency-based skills aligned with the digital economy. This study explores the integration of AI-driven adaptive learning systems in Uzbek technical schools and colleges, focusing on their pedagogical effectiveness and practical outcomes. The findings demonstrate that AI- supported learning environments significantly improve students’ technical and cognitive competencies, promote personalized learning experiences, and enhance their readiness for the evolving labor market. The research highlights the strategic importance of AI in modernizing vocational education and fostering a competitive, digitally skilled workforce.